Organotin(IV) complexes of 2-hydroxyacetophenone-N(4)-cyclohexylthiosemicarbazone (H(2)dact): synthesis, spectral characterization, crystal structure and biological studies - Affan, M.A.; Salam, M.A.; Ahmad, F.B.; White, Fraser; Ali, Hapipah Mohd (Elsevier, 2012)
Four new organotin(IV) complexes of the type [MeSnCl(dact)] (2), [BuSnCl(dact)] (3), [PhSnCl(dact)] (4) and [Ph2Sn(dact)] (5) were synthesized by the direct reaction of 2-hydroxyacetophenone-N(4)-cyclohexylthiosemicarbazone [H(2)dact, (1)] and organotin(IV) chloride(s) in absolute methanol. The ligand [H(2)dact, (1)] and its organotin(IV) complexes (2-5) have been characterized by CHN analyses, molar conductivity, UV-Vis, FT-IR, H-1, C-13 and Sn-119 NMR spectral studies. The molecular structure of complex (5) has also been determined by single-crystal X-ray diffraction. The crystal structure of complex (5) showed that the ligand is doubly deprotonated at the oxygen and sulfur atoms and is coordinated to the tin(IV) atom through thiolate-S, azomethine-N and phenoxide-O atoms. X-ray diffraction studies indicated that complex (5) is a monomer and the central tin(IV) atom is five coordinated in a distorted trigonal bipyramidal geometry. The cytotoxicity of the ligand (1) as well as its organotin(IV) complexes (2-5) was studied against Artemia salina. The in vitro antibacterial activities of these compounds were also evaluated. The screening results have shown that the organotin(IV) complexes (2-5) have better antibacterial activity than the free ligand. Furthermore, it has been shown that diphenyltin(IV) derivative (5) exhibits significantly better activity than the monoorganotin(IV) derivatives (2-4). (C) 2012 Elsevier B.V. All rights reserved.